Reprocessing Zamak laryngoscope blades into new instrument parts; an 'all-in-one' experimental study. Issue 11 (November 2022) - van Straten, Bart; Tantuo, Brian; Dankelman, Jenny; Sperna Weiland, Nicolaas H.; Boersma, Bendiks Jan; Horeman, Tim
Abstract: Introduction: Disposable instruments in healthcare have led to a significant increase of medical waste. The aim of this study is to validate the recycling of disposable Zamak laryngoscope blades into new medical components by using a new 'all-in-one' affordable reprocessing setup as alternative for die-casting. Methods: A n "all-in-one" casting set-up was designed and built. Laryngoscope blades, recovered from two hospitals, were disinfected, melted and cast into dog-bones and into new instrument parts. The quality of the cast material was evaluated using X-ray fluorescence spectrometry. The mechanical properties were obtained by assessing the Ultimate Tensile Strength (UTS) and tensile tests. Results: A recovery of 93 % Zamak was obtained using a melting temperature of 420 °C for 3 h. The XRF Spectro data showed higher Zinc and silicon concentrations when compared with Virgin Zamak. The dog-bones tests resulted in an average UTS, Yield Strength (YS) and Young's Modulus (YM) of 236 ± 61 (MPa), 70 ± 43 and 9 ± 3, respectively, representing 82 %, 103 % and 64 % of the UTS, YS and YM of standard Zamak. Functional instrument parts with extensions and inner chambers were cast with a maximal shrinkage percentage of 1 ± 1 %. Discussion: This study demonstrates that the created "all-in-one" reprocessing method can process contaminated disposable Zamak laryngoscope blades into new raw base material and new instrument parts. Although material and surface properties can deteriorate, reprocessed Zamak still has sufficient mechanical properties and can be used to cast complex parts with sufficient dimensional tolerances and minimal shrinkage. Conclusion: A micro reprocessing method was designed and used to turn disposed laryngoscope blades into new basis material and semi-finished components. Follow up studies are needed to scale and optimize this process towards a functional alternative for die casting. It should be further investigated how this process can contribute to further medical waste reduction and a circular healthcare economy. Abstract : Circular economy; Recycle; Sustainable production and consumption; Cleaner production; Sustainable business; Clean technology